Electromagnetic wave shielding material, electronic component, and electronic apparatus
By adopting a multi-layer structure of magnetic layer containing magnetic particles and resin in the electromagnetic wave shielding material, and using urethane bond-containing resin and epoxy resin in the magnetic layer, it is solved that it is difficult for existing materials to achieve high shielding performance and The problem of durability achieves efficient electromagnetic wave shielding and excellent durability.
Patent Information
- Application Number
- CN202380049792.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-09-07
- Filing Date
- 2023-06-26
- Publication Date
- 2025-02-11
AI Technical Summary
It is difficult for existing electromagnetic wave shielding materials to achieve high shielding performance and durability at the same time, especially to maintain good performance after external stress.
A multi-layer structure in which a magnetic layer containing magnetic particles and resin is sandwiched between two metal layers. Specifically, the total mass of the magnetic layer is 100 parts by mass, and 13 parts by mass or more and less than 30 parts by mass. Carbamate-bonded resin, and epoxy resin is added to the magnetic layer to improve adhesion and fracture resistance.
It achieves high shielding performance and excellent durability, can maintain good performance after external stress, and is suitable for various electronic parts and electronic equipment.
Smart Images

Figure BDA0005208578150000271 
Figure HDA0005208578160000011 
Figure HDA0005208578160000021
Abstract
Description
Technical Field
[0001] The invention relates to an electromagnetic wave shielding material, an electronic component and an electronic device. Background Art
[0002] Patent Document 1 discloses a noise suppression sheet including a sheet-shaped composite magnetic body.
[0003] Previous technical literature
[0004] Patent Literature
[0005] Patent Document 1: Japanese Patent Application Publication No. 2019-153623 Summary of the invention
[0006] Technical issues to be solved by the invention
[0007] In recent years, electromagnetic wave shielding materials have attracted attention as materials used to reduce the influence of electromagnetic waves in various electronic parts and various electronic devices. Electromagnetic wave shielding materials (hereinafter, also recorded as "shielding materials") can exert the performance of shielding electromagnetic waves (hereinafter, also recorded as "electromagnetic wave shielding performance" or "shielding performance") by causing electromagnetic waves incident on the shielding materials to be reflected by the shielding materials and / or attenuated inside the shielding materials. For example, the noise suppression sheet described in Patent Document 1 can function as an electromagnetic wave shielding material.
[0008] Electromagnetic wave shielding materials are required to have high shielding performance. Electromagnetic wave shielding materials that have high shielding performance against electromagnetic waves can help significantly reduce the impact of electromagnetic waves in electronic parts and electronic devices.
[0009] Furthermore, electromagnetic wave shielding materials are sometimes subjected to external forces during molding, and even after being assembled into electronic parts or electronic devices after molding, they are sometimes subjected to external forces due to, for example, being dropped or bumped, etc. Having durability that can withstand such external forces can also be listed as a desired performance of electromagnetic wave shielding materials.
[0010] In view of the above circumstances, an object of one embodiment of the present invention is to provide an electromagnetic shielding material that can exhibit high shielding performance and has excellent durability.
[0011] Means for solving technical problems
[0012] One embodiment of the present invention is as follows.
[0013] [1] An electromagnetic wave shielding material having a magnetic layer containing magnetic particles and a resin between two metal layers,
[0014] The magnetic layer is in direct contact with each of the two metal layers, and
[0015] The magnetic layer contains 13 parts by mass or more and less than 30 parts by mass of the urethane bond-containing resin, based on 100 parts by mass of the total mass of the magnetic layer.
[0016] [2] The electromagnetic wave shielding material according to [1], wherein
[0017] The magnetic layer contains 15 parts by mass or more and 23 parts by mass or less of the urethane bond-containing resin, based on 100 parts by mass of the total mass of the magnetic layer.
[0018] [3] The electromagnetic wave shielding material according to [1] or [2], wherein
[0019] The glass transition temperature of the urethane bond-containing resin is -60°C or higher and lower than 0°C.
[0020] [4] The electromagnetic wave shielding material according to any one of [1] to [3], wherein
[0021] The magnetic layer further contains epoxy resin.
[0022] [5] The electromagnetic wave shielding material according to [4], wherein
[0023] When the total mass of the magnetic layer is 100 parts by mass, the total content of the urethane bond-containing resin and the epoxy resin in the magnetic layer is 15 parts by mass or more and 20 parts by mass or less.
[0024] [6] An electromagnetic wave shielding material according to any one of [1] to [5], comprising two or more multilayer structures having the magnetic layer between two metal layers, wherein in each multilayer structure, the magnetic layer is in direct contact with each of the two metal layers.
[0025] [7] The electromagnetic wave shielding material according to any one of [1] to [6], wherein
[0026] One or more of the metal layers has a Cu content of 80.0 mass % or more.
[0027] [8] The electromagnetic wave shielding material according to any one of [1] to [7], wherein
[0028] One or more of the metal layers has an Al content of 80.0 mass % or more.
[0029] [9] The electromagnetic wave shielding material according to [1], wherein
[0030] The magnetic layer contains 15 parts by mass or more and 23 parts by mass or less of the urethane bond-containing resin, based on 100 parts by mass of the total mass of the magnetic layer.
[0031] The glass transition temperature of the urethane bond-containing resin is not less than -60°C and less than 0°C.
[0032] The electromagnetic wave shielding material comprises two or more multilayer structures having the magnetic layer between two metal layers, wherein in each multilayer structure, the magnetic layer is in direct contact with each of the two metal layers, and
[0033] One or more of the metal layers has a Cu content of 80.0 mass % or more.
[0034]
[10] The electromagnetic wave shielding material according to [1], wherein
[0035] The magnetic layer contains 15 parts by mass or more and 23 parts by mass or less of the urethane bond-containing resin, based on 100 parts by mass of the total mass of the magnetic layer.
[0036] The glass transition temperature of the urethane bond-containing resin is not less than -60°C and less than 0°C.
[0037] The electromagnetic wave shielding material comprises two or more multilayer structures having the magnetic layer between two metal layers, wherein in each multilayer structure, the magnetic layer is in direct contact with each of the two metal layers, and
[0038] One or more of the metal layers has an Al content of 80.0 mass % or more.
[0039]
[11] The electromagnetic wave shielding material according to [1], wherein
[0040] The magnetic layer further contains epoxy resin.
[0041] When the total mass of the magnetic layer is 100 parts by mass, the total content of the urethane bond-containing resin and the epoxy resin in the magnetic layer is 15 parts by mass or more and 20 parts by mass or less.
[0042] The glass transition temperature of the resin containing urethane bonds is not less than -60°C and less than 0°C, the electromagnetic wave shielding material comprises two or more multilayer structures having the magnetic layer between two metal layers, in each multilayer structure, the magnetic layer is in direct contact with each of the two metal layers, and
[0043] One or more of the metal layers has a Cu content of 80.0 mass % or more.
[0044]
[12] An electronic component comprising the electromagnetic wave shielding material according to any one of [1] to
[11] .
[0045]
[13] An electronic device comprising the electromagnetic wave shielding material according to any one of [1] to
[11] .
[0046] Effects of the Invention
[0047] According to one aspect of the present invention, it is possible to provide an electromagnetic wave shielding material that can exhibit high shielding performance and is excellent in durability. In addition, according to one aspect of the present invention, it is possible to provide an electronic component and an electronic device including the electromagnetic wave shielding material. BRIEF DESCRIPTION OF THE DRAWINGS
[0048] Figure 1 This is an explanatory diagram related to the measurement of peel strength.
[0049] Figure 2 This is an explanatory diagram related to the measurement of peel strength. DETAILED DESCRIPTION
[0050] [Electromagnetic wave shielding materials]
[0051] One embodiment of the present invention relates to an electromagnetic wave shielding material, which has a magnetic layer containing magnetic particles and a resin between two metal layers, the magnetic layer is in direct contact with each of the two metal layers, and the magnetic layer contains more than 13 parts by mass and less than 30 parts by mass of a resin containing a carbamate bond, and the total mass of the magnetic layer is set to 100 parts by mass.
[0052] In the present invention and this specification, "electromagnetic wave shielding material" refers to a material that can show shielding performance against electromagnetic waves of at least one frequency or at least a part of the frequency band. "Electromagnetic waves" include magnetic field waves and electric field waves. "Electromagnetic wave shielding material" is preferably a material that can show shielding performance against one or both of magnetic field waves of at least one frequency or at least a part of the frequency band and electric field waves of at least one frequency or at least a part of the frequency band.
[0053] In the present invention and this specification, "magnetism" refers to ferromagnetism (ferromagnetic property). The magnetic layer will be described in detail later.
[0054] In the present invention and this specification, "metal layer" refers to a layer containing metal. The metal layer may be a layer containing one or more metals, and the one or more metals may be a pure metal composed of a single metal element, an alloy of two or more metal elements, or an alloy of one or more metal elements and one or more non-metal elements. The metal layer will be described in detail later.
[0055] In the present invention and this specification, the term “direct contact” between the magnetic layer and the metal layer means that the magnetic layer and the metal layer are directly adjacent to each other without any other layer interposed therebetween.
[0056] Regarding the above-mentioned electromagnetic wave shielding material, the inventor speculates that the reason why the above-mentioned electromagnetic wave shielding material can exert high shielding performance against electromagnetic waves is that the above-mentioned electromagnetic wave shielding material has a multilayer structure with a magnetic layer sandwiched between two metal layers. The details are as follows. In order to obtain high shielding performance against electromagnetic waves in the electromagnetic wave shielding material, it is preferred to increase the reflection at the interface in addition to improving the attenuation ability of electromagnetic waves. That is, it is preferred that the electromagnetic wave is greatly attenuated by repeatedly reflecting at the interface and passing through the shielding material many times. However, as for the behavior of the metal layer and the magnetic layer to electromagnetic waves, the metal layer has a tendency that the attenuation ability of electromagnetic waves is large but the reflection of the magnetic field wave at the interface is small, and the magnetic layer has a tendency that the attenuation ability of electromagnetic waves is smaller than that of the metal layer but the reflection of the magnetic field wave at the interface is greater than that of the metal layer. Therefore, it is not easy to take into account both high reflection and attenuation for electromagnetic waves, especially magnetic field waves, by relying solely on the metal layer or the magnetic layer. In contrast, the above-mentioned electromagnetic wave shielding material can take into account both the reflection at the interface and the attenuation within the layer by including a multilayer structure with a magnetic layer between two metal layers. The inventor believes that this is the reason why the above-mentioned electromagnetic wave shielding material can exert high shielding performance against magnetic field waves. However, the present invention is not limited to the speculation described in this specification.
[0057] Moreover, in the above-mentioned multilayer structure, the magnetic layer directly contacting each of the two metal layers contains 13 parts by mass or more and less than 30 parts by mass of a resin containing a urethane bond, based on 100 parts by mass of the total mass of the magnetic layer. The inventors believe that this helps the above-mentioned electromagnetic wave shielding material to exert high shielding performance and to show excellent durability. This will be described in detail later.
[0058] Hereinafter, the above-mentioned electromagnetic wave shielding material will be described in further detail.
[0059] <Magnetic layer>
[0060] The magnetic layer contains magnetic particles and resin.
[0061] (Magnetic Particles)
[0062] As magnetic particles, one selected from the group consisting of magnetic particles generally referred to as soft magnetic particles, such as metal particles and ferrite particles, or a combination of two or more can be used. Metal particles generally have a saturation magnetic flux density of about 2 to 3 times that of ferrite particles, so they will not be magnetically saturated even in a strong magnetic field and maintain relative magnetic permeability to show shielding performance. Therefore, the magnetic particles contained in the magnetic layer are preferably metal particles. In the present invention and this specification, the layer containing metal particles as magnetic particles belongs to the "magnetic layer".
[0063] Metal particles
[0064] As metal particles of the above-mentioned magnetic particles, for example, particles such as sendust (Fe-Si-Al alloy), permalloy (Fe-Ni alloy), molybdenum permalloy (Fe-Ni-Mo alloy), Fe-Si alloy, Fe-Cr alloy, Fe-containing alloy commonly known as iron-based amorphous alloy, Co-containing alloy commonly known as cobalt-based amorphous alloy, alloy commonly known as nanocrystalline alloy, iron, permendur (Fe-Co alloy) can be cited. Among them, sendust shows high saturation magnetic flux density and relative magnetic permeability, so it is preferred. In addition to containing the constituent elements of the metal (including alloy), the metal particles can also contain elements contained in additives that can be added arbitrarily and / or elements contained in impurities that may be accidentally mixed in the manufacturing process of the metal particles at any content rate. The content rate of the constituent elements of the metal (including alloy) in the metal particles is preferably 90.0 mass% or more, more preferably 95.0 mass% or more, and can be 100 mass%, less than 100 mass%, 99.9 mass% or less, or 99.0 mass% or less.
[0065] In one embodiment, the shielding performance of an electromagnetic wave shielding material against electromagnetic waves can be evaluated using the magnetic permeability (specifically, the real part of the complex relative magnetic permeability) of a magnetic layer contained in the electromagnetic wave shielding material as an indicator. An electromagnetic wave shielding material having a magnetic layer showing high magnetic permeability (specifically, the real part of the complex relative magnetic permeability) can exhibit high shielding performance against electromagnetic waves and is therefore preferred.
[0066] When the complex relative magnetic permeability is measured by a magnetic permeability measuring device, the real part μ' and the imaginary part μ" are usually displayed. The real part of the complex relative magnetic permeability in the present invention and this specification refers to the real part μ'. Hereinafter, the real part of the complex relative magnetic permeability at a frequency of 3 MHz (megahertz) is also referred to as "magnetic permeability" or "magnetic permeability μ'". The magnetic permeability can be measured by a commercially available magnetic permeability measuring device or a magnetic permeability measuring device of a known structure. The measurement temperature is set to 25°C. By setting the ambient temperature of the measuring sample to the measurement temperature, the temperature equilibrium is established and the real part of the complex relative magnetic permeability is measured. The temperature of the sample for measurement is set to the measurement temperature. From the viewpoint of being able to exert further excellent electromagnetic wave shielding performance, the magnetic permeability (real part of complex relative magnetic permeability at a frequency of 3 MHz) of the magnetic layer contained in the above-mentioned electromagnetic wave shielding material is preferably 40 or more, more preferably 100 or more, and further preferably 120 or more. In addition, the above-mentioned magnetic permeability can be, for example, less than 500, less than 300, or less than 200, and can also be higher than the value exemplified here. The above-mentioned electromagnetic wave shielding material with high magnetic permeability can exert excellent electromagnetic wave shielding performance, and is therefore preferred.
[0067] From the viewpoint of forming a magnetic layer showing high magnetic permeability, the magnetic particles are preferably particles with a flat shape (flat particles), more preferably metal particles with a flat shape. By configuring the long side direction of the flat particles to be closer to parallel with the in-plane direction of the magnetic layer so that the long side direction of the particles is further consistent with the vibration direction of the electromagnetic wave orthogonally incident with respect to the electromagnetic wave shielding material, the diamagnetic field can be reduced, so the magnetic layer can show a higher magnetic permeability. In the present invention and this specification, "flat particles" refer to particles with an aspect ratio of less than 0.20. The aspect ratio of the flat particles is preferably less than 0.15, more preferably less than 0.10. The aspect ratio of the flat particles can be, for example, more than 0.01, more than 0.02 or more than 0.03. For example, by using a known method for flattening, the shape of the particles can be made into a flat shape. Regarding flattening, for example, reference can be made to the records of Japanese Patent Publication No. 2018-131640, for example, reference can be made to the records of paragraphs 0016 and 0017 of the publication and the embodiments. An example of a magnetic layer having a high magnetic permeability is a magnetic layer containing flat particles of Sendust.
[0068] As described above, from the viewpoint of forming a layer showing high magnetic permeability as a magnetic layer, it is preferred to arrange the long side direction of the flat particles to be closer to parallel with respect to the in-plane direction of the magnetic layer. From this point of view, the absolute value of the average value of the orientation angle of the flat particles relative to the surface of the magnetic layer and the dispersion of the orientation angle, that is, the orientation degree is preferably 30° or less, more preferably 25° or less, further preferably 20° or less, and further preferably 15° or less. The orientation degree can be, for example, 3° or more, 5° or more, or 10° or more, or it can be lower than the values exemplified here. The method for controlling the orientation degree will be described later.
[0069] In the present invention and this specification, the aspect ratio of the magnetic particles and the above-mentioned orientation degree are obtained by the following method.
[0070] The cross section of the magnetic layer was exposed by a known method. A cross section image was acquired as a scanning electron microscope (SEM) image of a randomly selected region of the cross section. The imaging conditions were set to an acceleration voltage of 2 kV and a magnification of 1000 times, and the SEM image was obtained as a reflected electron image.
[0071] The cv2.imread() function of the image processing library OpenCV4 (manufactured by Intel Corporation) was used, the second independent variable was set to 0 and read out in grayscale, and the middle brightness of the high brightness part and the low brightness part was used as the boundary, and the binary image was obtained using the cv2.threshold() function. The white part (high brightness part) in the binary image was determined as the magnetic particle.
[0072] For the obtained binary image, the rotated circumscribed rectangle corresponding to each magnetic particle part is obtained by cv2.minAreaRect() function, and the long side length, short side length and rotation angle are obtained by using it as the return value of cv2.minAreaRect() function. When the total number of magnetic particles contained in the above binary image is obtained, particles in which only a part of the particles is included in the binary image are also included. For particles in which only a part of the particles is included in the binary image, the long side length, short side length and rotation angle are obtained for the part included in the binary image. The ratio of the short side length to the long side length (short side length / long side length) thus obtained is set as the aspect ratio of each magnetic particle. In the present invention and this specification, when the aspect ratio is less than 0.20 and the number of magnetic particles determined to be flat particles is more than 10% based on the number of the total number of magnetic particles contained in the above binary image, the magnetic layer is judged as a "magnetic layer containing flat particles as magnetic particles". Then, from the rotation angle obtained above, the "orientation angle" is obtained as a rotation angle with respect to the horizontal plane (the surface of the magnetic layer).
[0073] The particles with an aspect ratio of 0.20 or less obtained in the binarized image are determined as flat particles. For the orientation angles of all flat particles contained in the binarized image, the absolute value of the average value (arithmetic mean) and the sum of the variance are obtained. The sum thus obtained is set as "degree of orientation". In addition, the coordinates of the circumscribed rectangle are calculated using the cv2.boxPoints() function, and the image obtained by superimposing the rotated circumscribed rectangle on the original image is produced by the cv2.drawContours() function, and the rotated circumscribed rectangle that is obviously misdetected is excluded from the calculation of the aspect ratio and the degree of orientation. In addition, the average value (arithmetic mean) of the aspect ratio of the particles determined as flat particles is set as the aspect ratio of the flat particles contained in the magnetic layer of the measurement object. The aspect ratio is less than 0.20, preferably less than 0.15, and more preferably less than 0.10. In addition, the above-mentioned aspect ratio can be, for example, more than 0.01, more than 0.02 or more than 0.03.
[0074] When the total mass of the magnetic layer is set to 100 parts by mass, the content of magnetic particles in the above-mentioned magnetic layer can be, for example, more than 50 parts by mass, more than 60 parts by mass, more than 70 parts by mass, or more than 80 parts by mass, and, for example, can be less than 87 parts by mass, less than 85 parts by mass, less than 80 parts by mass, or less than 75 parts by mass. The above-mentioned magnetic layer may contain only one kind of magnetic particles, or may contain two or more kinds of magnetic particles in any proportion. In the present invention and this specification, when a certain component contains two or more kinds, the content refers to the total content of these components. The content of various components in the magnetic layer can be obtained by TG / DTA (Thermogravimetry / Differentia1 Thermal Analysis: thermogravimetry-differential thermal analysis), using solvents to extract various components and other well-known methods. In addition, "TG / DTA" is generally referred to as thermogravimetric differential thermal analysis. When the composition of the magnetic layer forming composition used to form the magnetic layer is known, the content of various components in the magnetic layer can also be obtained based on the known composition.
[0075] In one embodiment, the magnetic layer may be an insulating layer. In the present invention and this specification, "insulating" means that the electrical conductivity is less than 1S (Siemens) / m. The electrical conductivity of a certain layer is calculated by the following formula based on the surface resistivity of the layer and the thickness of the layer. The electrical conductivity can be measured by a known method.
[0076] Electrical conductivity [S / m] = 1 / (surface resistivity [Ω] × thickness [m])
[0077] The inventors speculate that the fact that the magnetic layer is an insulating layer is preferred from the perspective that the electromagnetic wave shielding material can exert a higher electromagnetic wave shielding performance. From this point of view, the conductivity of the magnetic layer is preferably less than 1 S / m, more preferably less than 0.5 S / m, further preferably less than 0.1 S / m, and further preferably less than 0.05 S / m. The conductivity of the magnetic layer can be, for example, 1.0×10 -12 S / m or above or 1.0×10 -10 S / m and above.
[0078] (resin)
[0079] The magnetic layer is a layer containing magnetic particles and resin. The resin can act as an adhesive in the magnetic layer. In the present invention and this specification, the layer containing both magnetic particles and resin belongs to the "magnetic layer". In the present invention and this specification, "resin" means a polymer, and also includes rubber and elastomer. Polymers include homopolymers and copolymers. Rubber includes natural rubber and synthetic rubber. And, elastomers are polymers that show elastic deformation.
[0080] Resins containing urethane bonds
[0081] The magnetic layer contains a resin containing a carbamate bond. In the present invention and this specification, "a resin containing a carbamate bond" refers to a resin containing one or more carbamate bonds (-NH-C(=O)O-) in one molecule. The resin containing a carbamate bond includes various resins containing carbamate bonds such as polyurethane resins, polyester carbamate resins, and polyurethane elastomers. In the magnetic layer, a single polyurethane resin can be used, or two or more polyurethane resins can be used in combination. In addition, the type of resin contained in the magnetic layer can be determined by organic analysis such as thermal decomposition GC / MS (Gas Chromatography / Massspectrometry) and Fourier transform infrared spectroscopy. For example, when isocyanate component residues and / or polyol component residues are observed by thermal decomposition GC / MS, it can be determined as a resin containing a carbamate bond.
[0082] From the perspective of improving the adhesion of the metal layer in direct contact with the magnetic layer, when the total mass of the magnetic layer is set to 100 parts by mass, the content of the resin containing a carbamate bond in the magnetic layer is 13 parts by mass or more, preferably 14 parts by mass or more, more preferably 15 parts by mass or more, further preferably 16 parts by mass or more, and further preferably 17 parts by mass or more. If the adhesion of the metal layer in direct contact with the magnetic layer is high, it is not easy to peel off between the magnetic layer and the metal layer when the electromagnetic wave shielding material is subjected to force from the outside. If the occurrence of such peeling can be suppressed, the durability of the electromagnetic wave shielding material will be improved, so it is preferred. In addition, from the perspective of improving the shielding performance of the electromagnetic wave shielding material, when the total mass of the magnetic layer is set to 100 parts by mass, the content of the resin containing a carbamate bond in the magnetic layer is less than 30 parts by mass, preferably 29 parts by mass or less, and more preferably 28 parts by mass or less, 27 parts by mass or less, 26 parts by mass or less, 25 parts by mass or less, 24 parts by mass or less, and 23 parts by mass or less.
[0083] The electromagnetic wave shielding material can be bent into any shape for use. If the magnetic layer breaks when the shielding material is bent, the shielding performance may be reduced at the break, so it is preferred that the magnetic layer has excellent fracture resistance and is not easy to break when bent. From the viewpoint of improving the fracture resistance of the magnetic layer, as the magnetic layer, it is preferred to contain a layer of a resin containing a carbamate bond with a glass transition temperature Tg of less than 0°C. In the present invention and this specification, the glass transition temperature Tg is obtained as the starting temperature of the baseline shift of the heat flow diagram when the temperature is increased based on the measurement results of the heat flow measurement measured using a differential scanning calorimeter. From the viewpoint of further improving the fracture resistance of the magnetic layer, the glass transition temperature Tg of the resin containing a carbamate bond contained in the magnetic layer is more preferably below -3°C, more preferably below -5°C, and more preferably below -10°C, below -20°C, below -30°C, and below -40°C, respectively. Furthermore, the glass transition temperature Tg of the resin contained in the magnetic layer may be, for example, -100°C or higher, -90°C or higher, -80°C or higher, -70°C or higher, or -60°C or higher.
[0084] The resin contained in the magnetic layer may be only a resin containing a carbamate bond, or, in addition to the resin containing a carbamate bond, may contain one or more other resins in any amount. The content of the resin containing a carbamate bond may be, for example, 80 parts by mass or more, 85 parts by mass or more, 90 parts by mass or more, or 95 parts by mass or more relative to 100 parts by mass of the total amount of the resin in the magnetic layer, and may be 100 parts by mass, or may be less than 100 parts by mass, less than 100 parts by mass, less than 99 parts by mass, or less than 98 parts by mass.
[0085] Epoxy resin
[0086] In addition to the resin containing the urethane bond, the magnetic layer may also contain an epoxy resin. In the present invention and this specification, "epoxy resin" refers to a resin containing one or more epoxy groups in one molecule. In the magnetic layer containing the epoxy resin, at least a part of the epoxy groups possessed by the epoxy resin may be contained in the magnetic layer in an open-ring manner. As the epoxy resin, known epoxy resins such as the glycidyl ether type, the glycidyl ester type, the glycidyl amine type, and the oxidized type may be used alone or in combination of two or more. As the glycidyl ether type, Bis-A type epoxy resin, Bis-F type epoxy resin, High-Br type epoxy resin, novolac type epoxy resin, alcohol type epoxy resin, etc. may be cited. As the glycidyl ester type, hydrogenated phthalic acid (hydrophthalic) type epoxy resin, dimer acid type epoxy resin, etc. may be cited. As the glycidyl amine type, aromatic amine type epoxy resin, aminophenol type epoxy resin, etc. may be cited. As the oxidized type, alicyclic epoxy resins, etc. may be cited. From the viewpoint of imparting flexibility to electromagnetic wave shielding materials, as epoxy resin, preferably, Bis-A type epoxy resin of glycidyl ether type having hydrocarbon chain is used. As the above-mentioned hydrocarbon chain, preferably, aliphatic hydrocarbon chain, more preferably, hydrocarbon chain with alkylene chain length of 3 or more. As a specific example of Bis-A type epoxy resin of glycidyl ether type having aliphatic hydrocarbon chain with alkylene chain length of 3 or more, HP-A-4860 manufactured by DIC Corporation can be cited.
[0087] In the case where the magnetic layer contains an epoxy resin, when the total mass of the magnetic layer is set to 100 parts by mass, the content of the epoxy resin in the magnetic layer exceeds 0 parts by mass, and may be 1 part by mass or more. From the perspective of the self-supporting property of the magnetic layer, it is preferably 10 parts by mass or less, more preferably 8 parts by mass or less, and further preferably 6 parts by mass or less. Furthermore, from the perspective of improving the adhesion with the metal layer in direct contact with the magnetic layer, when the total mass of the magnetic layer is set to 100 parts by mass, the total content of the resin containing a urethane bond and the resin containing an epoxy group in the magnetic layer is preferably 15 parts by mass or more, and from the perspective of improving the shielding performance of the electromagnetic wave shielding material, it is preferably 20 parts by mass or less.
[0088] The magnetic layer may contain any amount of one or more known additives such as a curing agent, a curing catalyst, a dispersant, a stabilizer, and a coupling agent in addition to the above components.
[0089] For example, as a curing agent, a compound having a crosslinking group can be cited. In the case where the curing agent is a compound having a crosslinking group, in the magnetic layer containing such a curing agent, the curing agent can be contained in the magnetic layer in the form of at least a part of the crosslinking group undergoing a crosslinking reaction. In the present invention and this specification, a "crosslinking group" refers to a group capable of undergoing a crosslinking reaction, and an isocyanate group can be cited as a specific example. In addition, as a curing agent, a compound having more than 2 (for example, more than 2 and less than 4) crosslinking groups in one molecule is preferred, and a polyfunctional isocyanate can be cited as a specific example. A polyfunctional isocyanate is a compound having more than 2 isocyanate groups in one molecule, for example, a compound having more than 2 and less than 4 isocyanate groups in one molecule. In one embodiment, when the resin contained in the magnetic layer is set to 100 parts by mass, the magnetic layer can contain more than 2.5 parts by mass or more than 10 parts by mass of a polyfunctional isocyanate. Furthermore, in one embodiment, when the resin contained in the magnetic layer is set to 100 parts by mass, the magnetic layer may contain 100 parts by mass or less or 40 parts by mass of the polyfunctional isocyanate. Furthermore, in one embodiment, when the urethane bond-containing resin contained in the magnetic layer is set to 100 parts by mass, the magnetic layer may contain 2.5 parts by mass or more or 10 parts by mass of the polyfunctional isocyanate. Furthermore, in one embodiment, when the urethane bond-containing resin contained in the magnetic layer is set to 100 parts by mass, the magnetic layer may contain 100 parts by mass or less or 40 parts by mass of the polyfunctional isocyanate.
[0090] <Metal Layer>
[0091] The electromagnetic wave shielding material has a multilayer structure including the magnetic layer between two metal layers. In the multilayer structure, the magnetic layer is a layer in direct contact with each of the two metal layers. The electromagnetic wave shielding material may include one or more such multilayer structures, and may also include two or more. That is, the electromagnetic wave shielding material includes at least two metal layers, and may also include three or more metal layers. The two or more metal layers included in the electromagnetic wave shielding material have the same composition and thickness in one embodiment, and different compositions and / or thicknesses in another embodiment. Furthermore, in the case where the electromagnetic wave shielding material includes more than two magnetic layers, the two or more magnetic layers have the same composition and thickness in one embodiment, and different compositions and / or thicknesses in another embodiment. A specific example of the layer structure of the electromagnetic wave shielding material will be described later.
[0092] As the metal layer, a layer containing one or more metals selected from a group consisting of various pure metals and various alloys can be used. The metal layer can exert an attenuation effect in the shielding material. The larger the propagation constant, the greater the attenuation effect, and the larger the conductivity, the larger the propagation constant, so the metal layer preferably contains a metal element with high conductivity. From this point of view, the metal layer preferably contains pure metals of Ag, Cu, Au or Al, or an alloy with any of these as the main component. Pure metal is a metal composed of a single metal element and may contain trace impurities. Generally, a metal with a purity of more than 99.0% composed of a single metal element is called a pure metal. Purity is a mass basis. Regarding alloys, one or more metal elements or non-metallic elements are usually added to pure metals to adjust the composition to prevent corrosion, increase strength, etc. The main component in the alloy refers to the component with the highest ratio based on the mass basis, for example, it can be a component that accounts for more than 80.0 mass% (for example, less than 100 mass% or less than 99.8 mass%) in the alloy. From the viewpoint of economic efficiency, pure metal Cu or Al, or an alloy containing Cu or Al as a main component is preferred, and from the viewpoint of high electrical conductivity, pure metal Cu or an alloy containing Cu as a main component is more preferred.
[0093] The purity of the metal in the metal layer, that is, the content of the metal relative to the total mass of the metal layer can be 99.0% by mass or more, preferably 99.5% by mass or more, and more preferably 99.8% by mass or more. Unless otherwise specified, the content of the metal in the metal layer refers to the content of the mass basis. For example, as a metal layer, a pure metal or alloy processed into a sheet can be used. For example, as a metal layer, a commercially available metal foil or a metal foil made by a known method can be used. Regarding the pure metal of Cu, thin sheets (so-called copper foil) of various thicknesses are commercially available. For example, such copper foil can be used as a metal layer. Among the copper foils, there are electrolytic copper foils obtained by electroplating copper foil to be precipitated on the cathode, and rolled copper foils obtained by applying heat and pressure to the ingot to roll it very thinly. Any copper foil can be used as the metal layer of the above-mentioned electromagnetic wave shielding material. And, for example, Al also has thin sheets (so-called aluminum foils) of various thicknesses commercially available. For example, such aluminum foils can be used as a metal layer.
[0094] From the perspective of lightweight electromagnetic wave shielding materials, one or two (preferably two) of the two metal layers contained in the above-mentioned multilayer structure are preferably metal layers containing a metal selected from the group consisting of Al and Mg. This is because the values obtained by dividing the specific gravity of Al and Mg by the conductivity (specific gravity / conductivity) are both small. The smaller the metal used, the lighter the electromagnetic wave shielding material that can exert high shielding performance. As values calculated based on literature values, for example, the values obtained by dividing the specific gravity of Cu, Al and Mg by the conductivity (specific gravity / conductivity) are as follows. Cu: 1.5×10-7 m / S,Al:7.6×10 -8 m / S,Mg:7.6×10 -8 m / S. According to the above values, it can be said that Al and Mg are preferred metals from the perspective of lightweight electromagnetic wave shielding materials. The metal layer comprising a metal selected from the group consisting of Al and Mg may include only one of Al and Mg in one embodiment, and may include both in another embodiment. From the perspective of lightweight electromagnetic wave shielding materials, one or two layers (preferably two layers) of the two metal layers included in the above-mentioned multilayer structure are more preferably a metal layer having a content of 80.0% by mass or more of the metal selected from the group consisting of Al and Mg, and more preferably a metal layer having a content of 90.0% by mass or more of the metal selected from the group consisting of Al and Mg. The metal layer containing at least Al in Al and Mg may be a metal layer having an Al content of 80.0% by mass or more, or may be a metal layer having an Al content of 90.0% by mass or more. The metal layer containing at least Mg in Al and Mg may be a metal layer having an Mg content of 80.0% by mass or more, or may be a metal layer having an Mg content of 90.0% by mass or more. The content of the metal selected from the group consisting of Al and Mg, the Al content, and the Mg content, for example, may be less than 100 mass % or less than 99.9 mass %. The content of the metal selected from the group consisting of Al and Mg, the Al content, and the Mg content, respectively, are the content ratios relative to the total mass of the metal layer.
[0095] In one embodiment, one or more of the above-mentioned metal layers can be metal layers with a Cu content of 80.0% by mass or more. The Cu content of the layer can be 90.0% by mass or more, and can be 99.9% by mass or less. In addition, in one embodiment, one or more of the above-mentioned metal layers can be metal layers with an Al content of 80.0% by mass or more. The Al content of the layer can be 90.0% by mass or more, and can be less than 100% by mass or 99.9% by mass or less. The Cu content and the Al content are the contents relative to the total mass of the metal layer, respectively. In one embodiment, the metal layers contained in the above-mentioned electromagnetic wave shielding material can all be metal layers with a Cu or Al content within the above-mentioned range.
[0096] <Specific example of layer structure>
[0097] As specific examples of the layer structure of the electromagnetic wave shielding material, the following examples can be given.
[0098] Example 1: "Metal layer / magnetic layer / metal layer"
[0099] Example 2: “metal layer / magnetic layer / metal layer / magnetic layer / metal layer”
[0100] Example 3: “metal layer / magnetic layer / metal layer / magnetic layer / metal layer / magnetic layer / metal layer”
[0101] In an electromagnetic wave shielding material having a multilayer structure including the above-mentioned magnetic layer between two metal layers, for example, as shown in Examples 2 and 3, a metal layer sandwiching a magnetic layer in a certain multilayer structure is also a metal layer sandwiching a magnetic layer in another multilayer structure. In the above-mentioned electromagnetic wave shielding material, the total number of multilayer structures including the above-mentioned magnetic layer between two metal layers can be, for example, 1 to 4. The total number of the above-mentioned multilayer structures is 1 in Example 1, 2 in Example 2, and 3 in Example 3. From the perspective of further improving the shielding performance of the electromagnetic wave shielding material, it is preferred that the total number of the above-mentioned multilayer structures is 2 or more (for example, 2, 3 or 4). In the above, the symbol " / " indicates that the layer recorded on the left side of the symbol is directly in contact with the layer recorded on the right side without passing through other layers. The total number of magnetic layers contained in the above-mentioned electromagnetic wave shielding material is one or more layers, and can also be two or more layers, and, for example, can be four or less layers. On the other hand, the total number of metal layers contained in the above-mentioned electromagnetic wave shielding material is two or more layers, for example, can be two to five layers.
[0102] <Various thicknesses>
[0103] Regarding the thickness of the metal layer, from the perspective of the processability of the metal layer and the shielding performance of the electromagnetic wave shielding material, the thickness of each layer is preferably 4 μm or more, more preferably 5 μm or more, further preferably 10 μm or more, further preferably 15 μm or more, further preferably 20 μm or more, and further preferably 25 μm or more. On the other hand, regarding the thickness of the metal layer, from the perspective of the processability of the metal layer, the thickness of each layer is preferably 100 μm or less, more preferably 50 μm or less, further preferably 45 μm or less, and further preferably 40 μm or less.
[0104] If the thickness of one of the two metal layers sandwiching the magnetic layer is set to T1, and the thickness of the other metal layer is set to T2, and T1 is greater than T2 (i.e., T1=T2 or T1>T2), then the thickness ratio of the two metal layers (T2 / T1) can be, for example, greater than 0.10. From the perspective of being able to exhibit higher shielding performance against magnetic field waves, it is preferably greater than 0.15, more preferably greater than 0.30, further preferably greater than 0.50, further preferably greater than 0.70, and further preferably greater than 0.80. From the perspective of being able to exhibit higher shielding performance against magnetic field waves, the smaller the difference between T1 and T2, the more preferred. The thickness ratio (T2 / T1) can be less than 1.00, or it can be 1.00 (i.e., T1=T2). In the case where the above-mentioned electromagnetic wave shielding material includes more than two multilayer structures having the above-mentioned magnetic layer between two metal layers, the above-mentioned records related to the thickness ratio (T2 / T1) can be applicable to at least one of the above-mentioned multilayer structures contained in the above-mentioned electromagnetic wave shielding material, and can also be applicable to more than two or all of them.
[0105] The shielding material can be bent into any shape according to the purpose. If the width of the bent portion (hereinafter referred to as "bend width") becomes wider when the shielding material is bent, the shape of the bent portion becomes a gentle curve shape, which is sometimes difficult to process into the target shape. From this point of view, the narrower the above-mentioned bending width is, the more preferred it is. The thicker the total thickness of the metal layer contained in the shielding material, the wider the above-mentioned bending width tends to be. From the viewpoint of narrowing the bending width of the shielding material, the total thickness of the metal layer contained in the above-mentioned electromagnetic wave shielding material is preferably 100μm or less, more preferably 90μm or less, further preferably 80μm or less, further preferably 70μm or less, further preferably 60μm or less, further preferably 50μm or less, and further preferably 40μm or less. The total thickness of the metal layer contained in the above-mentioned electromagnetic wave shielding material can be, for example, 8μm or more or 10μm or more.
[0106] Regarding the thickness of the magnetic layer, from the perspective of the shielding performance of the electromagnetic wave shielding material, the thickness of each layer can be, for example, 3 μm or more, preferably 10 μm or more, and more preferably 20 μm or more. And, from the perspective of the processability of the electromagnetic wave shielding material, the thickness of each magnetic layer can be, for example, 90 μm or less, preferably 70 μm or less, and more preferably 50 μm or less. In the case where the electromagnetic wave shielding material includes more than two magnetic layers, the total thickness of the magnetic layers included in the electromagnetic wave shielding material can be, for example, 6 μm or more, and, for example, can be 180 μm or less.
[0107] Furthermore, the total thickness of the shielding material may be, for example, 250 μm or less. From the viewpoint of narrowing the above-mentioned bending width, it is also preferred that the total thickness of the shielding material is thinner. From this point of view, the total thickness of the above-mentioned electromagnetic wave shielding material is preferably 200 μm or less, more preferably 190 μm or less, and further preferably 170 μm or less. The total thickness of the above-mentioned electromagnetic wave shielding material may be, for example, 30 μm or more or 40 μm or more.
[0108] The thickness of each layer included in the electromagnetic shielding material is a value obtained by photographing a cross section exposed by a known method using a scanning electron microscope (SEM) and calculating the arithmetic average of thicknesses at five points randomly selected from the obtained SEM image.
[0109] <Method for producing electromagnetic wave shielding material>
[0110] (Magnetic Layer Formation Method)
[0111] Regarding the above-mentioned magnetic layer, for example, it can be prepared by drying the coating layer provided by coating the magnetic layer forming composition. The magnetic layer forming composition contains the components described above and can arbitrarily contain one or more solvents. As the solvent, various organic solvents can be cited, for example, ketone solvents such as acetone, methyl ethyl ketone, cyclohexanone, ethyl acetate, butyl acetate, cellosolve acetate, propylene glycol monomethyl ether acetate, carbitol acetate and other acetate ester solvents, cellosolve, butyl carbitol and other carbitols, toluene, xylene and other aromatic hydrocarbon solvents, dimethylformamide, dimethylacetamide, N-methylpyrrolidone and other amide solvents, etc. It is possible to use a solvent or two or more solvents selected in consideration of the solubility of the components used in the preparation of the magnetic layer forming composition in any ratio. The solvent content of the magnetic layer forming composition is not particularly limited and can be determined by considering the coating properties of the magnetic layer forming composition.
[0112] The magnetic layer forming composition can be prepared by mixing the various components in any order or mixing them simultaneously. Furthermore, as required, a known dispersing machine such as a ball mill, a bead mill, a sand mill, a roller mill, etc. can be used for dispersion treatment, and / or a known stirring machine such as a vibration stirrer can be used for stirring treatment.
[0113] The magnetic layer-forming composition can be applied, for example, to a support. Application can be performed using a known coating device such as a knife coater or a die coater. Application can also be performed in a so-called roll-to-roll method or in a batch method.
[0114] As a support for coating the composition for forming a magnetic layer, for example, films of various resins such as polyesters such as polyethylene terephthalate (PET) and polyethylene naphthalate (PEN), acrylics such as polycarbonate (PC) and polymethyl methacrylate (PMMA), cyclic polyolefins, triacetyl cellulose (TAC), polyether sulfide (PES), polyether ketone, and polyimide can be cited. For these resin films, reference can be made to paragraphs 0081 to 0086 of Japanese Patent Publication No. 2015-187260. As a support, a support whose surface (coated surface) is coated with the composition for forming a magnetic layer and subjected to a release treatment by a known method can be used. As one method of the release treatment, the formation of a release layer can be cited. For the release layer, reference can be made to paragraph 0084 of Japanese Patent Publication No. 2015-187260. In addition, as a support, a commercially available resin film that has been subjected to a release treatment can also be used. By using a support body whose coated surface has been subjected to a release treatment, the magnetic layer and the support body can be easily separated after film formation.
[0115] In one embodiment, the magnetic layer-forming composition can be directly applied onto the metal layer using the metal layer as a support. By directly applying the magnetic layer-forming composition onto the metal layer, the magnetic layer can be formed directly onto the metal layer without intervening other layers.
[0116] The coating layer formed by applying the magnetic layer forming composition can be dried by a known method such as heating or blowing hot air. The drying process can be performed, for example, under conditions that allow the solvent contained in the magnetic layer forming composition to volatilize. As an example, the drying process can be performed in a heated atmosphere at an atmosphere temperature of 80 to 150° C. for 1 minute to 2 hours.
[0117] Regarding the composition for forming a magnetic layer that contains a curing agent in addition to magnetic particles and a resin, the curing agent can refer to the above description. The curing treatment of the curing agent can be applied to the magnetic layer formed using the composition for forming a magnetic layer at any stage. As the curing treatment, heat treatment or light irradiation treatment can be performed according to the type of curing agent. For example, in the case where the curing treatment is a heat treatment, the heat treatment can be performed before the pressurization treatment described later in one embodiment, and can be performed after the pressurization treatment described later in another embodiment. According to the research of the present inventors, it was found that if the above-mentioned heat treatment is performed after the pressurization treatment, the magnetic permeability of the formed magnetic layer tends to increase. The above-mentioned heat treatment can be performed, for example, by keeping the magnetic layer before or after the pressurization treatment in an environment with an atmospheric temperature of 35°C or above (for example, 35°C or above and 150°C or below). The above-mentioned holding time can be set to 3 to 72 hours, for example.
[0118] The orientation degree of the flat particles described in the above can be controlled by the solvent type, solvent amount, liquid viscosity, coating thickness, etc. of the magnetic layer forming composition. For example, if the boiling point of the solvent is low, the value of the orientation degree tends to increase due to convection caused by drying. If the amount of solvent is small, the value of the orientation degree tends to increase due to physical interference between adjacent flat particles. On the other hand, if the liquid viscosity is low, the value of the orientation degree tends to decrease due to the rotation of the flat particles. If the coating thickness is thinned, the value of the orientation degree tends to decrease. In addition, performing the pressure treatment described later can help reduce the value of the orientation degree. By adjusting the above-mentioned various manufacturing conditions, the orientation degree of the flat particles can be controlled within the range described in the above.
[0119] (Pressure treatment of magnetic layer)
[0120] The magnetic layer can also be subjected to a pressure treatment after film formation. By subjecting the magnetic layer containing magnetic particles to a pressure treatment, the density of the magnetic particles in the magnetic layer can be increased, and a higher magnetic permeability can be obtained. In addition, the magnetic layer containing flat particles can be subjected to a pressure treatment to reduce the value of the orientation degree, and a higher magnetic permeability can be obtained.
[0121] The pressurization treatment can be performed by applying pressure in the thickness direction of the magnetic layer using a plate press, a roller press, or the like. The plate press can place the object to be pressed between two flat pressing plates arranged one above the other and apply pressure to the object by closing the two pressing plates together under mechanical or hydraulic pressure. The roller press can apply pressure by passing the object to be pressed between rotating pressing rollers arranged one above the other and applying mechanical or hydraulic pressure to the pressing rollers at this time, or by making the distance between the pressing rollers smaller than the thickness of the object to be pressed.
[0122] The pressure during the press treatment can be set arbitrarily. For example, in the case of a plate press, it is 1 to 50 N (Newton) / mm 2 In the case of a roller press, the linear pressure is, for example, 20 to 400 N / mm.
[0123] The pressing time can be set arbitrarily. When a plate press is used, the pressing time is, for example, 5 seconds to 4 hours. When a roller press is used, the pressing time can be controlled by the conveying speed of the object to be pressed, for example, the conveying speed is 10 cm / min to 200 m / min.
[0124] The material of the pressing plate and the pressing roller can be arbitrarily selected from metal, ceramic, plastic, rubber, and the like.
[0125] When performing the pressurization treatment, for example, the upper and lower pressing plates or one side pressing plates of the plate press, or one side roller of the upper and lower rollers of the roller press can be subjected to heat and pressure treatment. In the heat and pressure treatment, the magnetic layer can be softened by heating, thereby obtaining a high compression effect when pressure is applied. The temperature during heating can be set arbitrarily, for example, above 50°C and below 200°C. The temperature during the heating can be the internal temperature of the pressing plate or the roller. The temperature can be measured by a thermometer provided inside the pressing plate or the roller. In one embodiment, a heat treatment can be performed before or after the heat and pressure treatment as a curing treatment of the curing agent. Regarding the heat treatment, it is as described above.
[0126] After the plate press is heated and pressurized, the plate can be separated to remove the magnetic layer, for example, while the temperature of the plate is high. Alternatively, the plate can be cooled by water cooling, air cooling, etc. while maintaining the pressure, and then the plate can be separated to remove the magnetic layer.
[0127] In a roll press, the magnetic layer can be cooled by water cooling, air cooling, or the like immediately after pressurization.
[0128] The pressurization treatment may be repeated two or more times.
[0129] When the magnetic layer is formed on a release film, for example, the pressure treatment can be performed in a state where the magnetic layer is laminated on the release film. Alternatively, the pressure treatment can be performed as a single magnetic layer after the magnetic layer is peeled off from the release film.
[0130] (Lamination of metal layer and magnetic layer)
[0131] The adjacent metal layer and magnetic layer can be directly bonded without passing through other layers by applying pressure and heat, for example. Plate presses, roller presses, etc. can be used for bonding. During the bonding process, the contact between the magnetic layer and the surface of the metal layer is promoted by softening the magnetic layer, so that the two adjacent layers can be bonded. The pressure during bonding can be set arbitrarily. In the case of a plate press, for example, it is 1 to 50 N / mm 2 . In the case of a roller press, for example, the line pressure is 20 to 400 N / mm. The pressing time during crimping can be set arbitrarily. In the case of a plate press, for example, it is 5 seconds to 30 minutes. In the case of a roller press, it can be controlled by the conveying speed of the pressurized object, for example, the conveying speed is 10 cm / minute to 200 m / minute. The temperature during crimping can be selected arbitrarily, for example, above 50°C and below 200°C. The temperature during crimping can be, for example, the internal temperature of the pressing plate or the roller.
[0132] In the above-mentioned multilayer structure of the above-mentioned electromagnetic wave shielding material, the above-mentioned magnetic layer is in direct contact with the adjacent metal layer. In this way, compared with the method of laminating the two layers by inserting other layers such as adhesive layers and bonding layers, the method of laminating the two layers without passing through other layers is simple and preferred from the process aspect. On the other hand, in the lamination of layers for improving the adhesion between layers without inserting adhesive layers, bonding layers, etc., interlayer peeling tends to occur easily. In contrast, in the above-mentioned electromagnetic wave shielding material, the magnetic layer directly contacting the metal layer contains a resin containing a carbamate bond in the above-mentioned content. The inventors believe that this helps to improve the adhesion between the metal layer and the magnetic layer without inserting other layers. It is speculated that this is because the resin containing a carbamate bond contains a high polarity portion. However, the present invention is not limited to this speculation.
[0133] The electromagnetic wave shielding material may be in any shape such as a film (or sheet). For example, the electromagnetic wave shielding material in a film shape may be bent into any shape and incorporated into an electronic component or electronic device.
[0134] [Electronic parts]
[0135] One aspect of the present invention relates to an electronic component comprising the above-mentioned electromagnetic wave shielding material. As the above-mentioned electronic component, various electronic components such as electronic components, semiconductor components, capacitors, coils, cables, etc. contained in electronic devices such as mobile phones, mobile information terminals, and medical devices can be cited. The above-mentioned electromagnetic wave shielding material can be bent into any shape according to the shape of the electronic component and arranged inside the electronic component, or can be arranged as a covering material covering the outside of the electronic component. Alternatively, it can be processed into a cylindrical shape and arranged as a covering material covering the outside of the cable.
[0136] [Electronic equipment]
[0137] One aspect of the present invention relates to an electronic device comprising the above-mentioned electromagnetic wave shielding material. As the above-mentioned electronic device, electronic devices such as mobile phones, mobile information terminals, medical devices, electronic devices comprising various electronic parts such as semiconductor elements, capacitors, coils, cables, and electronic devices in which electronic parts are mounted on circuit boards, etc. can be cited. The electronic device can include the above-mentioned electromagnetic wave shielding material as a component of the electronic parts contained in the device. In addition, the above-mentioned electromagnetic wave shielding material can be configured inside the electronic device as a component of the electronic device, or can be configured as a covering material covering the outside of the electronic device. Alternatively, it can be processed into a cylindrical shape and configured as a covering material covering the outside of a cable.
[0138] As an example of the use of the above-mentioned electromagnetic wave shielding material, there can be cited the use of semiconductor packages on printed substrates covered with shielding materials. For example, "Electromagnetic Wave Shielding Technology in Semiconductor Packages" (Toshiba review Vol. 67 No. 2 (2012) P. 8) discloses a method of obtaining a high shielding effect by electrically connecting the side through-holes at the end of the package substrate to the inner surface of the shielding material when covering the semiconductor package with a shielding material. In order to perform such wiring, the outermost layer on the electronic component side of the shielding material is preferably a metal layer. Regarding the above-mentioned electromagnetic wave shielding material, in one method, one or two outermost layers of the shielding material can be a metal layer, so it can be preferably used when performing wiring as described above.
[0139] Example
[0140] Hereinafter, the present invention will be described in more detail based on examples. However, the present invention is not limited to the embodiments shown in the examples.
[0141] [Urethane bond-containing resin of magnetic layer]
[0142] The urethane bond-containing resins of the magnetic layer shown in Table 1 are the following resins. In Table 1, polyurethane resins are indicated as "polyurethane" and polyester urethane resins are indicated as "polyester urethane".
[0143] The polyurethane resin having a glass transition temperature Tg of -50°C was Nipporan 5120 manufactured by TOSOH CORPORATION.
[0144] The polyester urethane resin having a glass transition temperature Tg of -30°C is UR-6100 manufactured by TOYOBO CO., Ltd.
[0145] The polyester urethane resin having a glass transition temperature Tg of -3°C is UR-3200 manufactured by TOYOBO CO., Ltd.
[0146] The polyester urethane resin having a glass transition temperature Tg of 23°C is UR-8300 manufactured by TOYOBO CO., Ltd.
[0147] The glass transition temperatures of the urethane bond-containing resins shown in Table 1 are values determined by the following method.
[0148] The same resin (granular or powdered sample) as that used in the preparation of the magnetic layer-forming composition (coating liquid) was placed in an aluminum sample pan, sealed with a punch, and heat flow measurement was performed under the following conditions using Q100 manufactured by TA Instruments as a differential scanning calorimeter. Based on the measurement results, the glass transition temperature of the resin was determined as the baseline shift starting temperature of the heat flow diagram when the temperature was increased.
[0149] (Measurement conditions)
[0150] Scanning temperature: -80.0℃~200.0℃
[0151] Heating rate: 10.0℃ / min
[0152] [Example 1]
[0153] <Preparation of Magnetic Layer-Forming Composition (Coating Liquid)>
[0154] Add to plastic bottles
[0155] Fe-Si-Al flat magnetic particles (Fe-Si-Al alloy MFS-SUH manufactured by MKT Corp., Ltd.): 12 g
[0156] Polyester urethane resin (UR-6100 manufactured by TOYOBO CO., LTD., solid content concentration 45 mass %): 6.7 g
[0157] Polyfunctional isocyanate (Takenate D101E manufactured by Mitsui Chemicals, Inc., solid content concentration 75 mass %): 0.1 g
[0158] Cyclohexanone: 25g
[0159] The mixture was mixed for 12 hours using a vibration stirrer to prepare a coating solution. The content of the polyester urethane resin was the value shown in Table 1, based on 100 parts by mass of the total mass of the magnetic layer formed from the prepared magnetic layer-forming composition.
[0160] <Fabrication of Magnetic Layer>
[0161] (Film Formation of Magnetic Layer)
[0162] The coating liquid was applied to the release surface of a PET film (PET75-JOL manufactured by Nippa Corporation) that had undergone a release treatment using a knife coater with a coating gap of 300 μm, and dried in a drying device with an internal atmosphere temperature of 80° C. for 30 minutes, thereby forming a film-like magnetic layer on the above-mentioned PET film that had undergone a release treatment.
[0163] (Pressure treatment and heat treatment of magnetic layer)
[0164] The upper and lower plates of a plate press (mini test press manufactured by TOYO SEIKI CO., LTD.) were heated to 140°C (internal temperature of the platen), and the magnetic layer of the PET film peeled off was sandwiched between two 1 mm thick Teflon (registered trademark) sheets, and a pressure of 30 N / mm was applied. 2 The pressure was maintained for 10 minutes. After the upper and lower pressing plates were cooled to 50° C. (internal temperature of the pressing plates) while the pressure was maintained, the magnetic layer was removed from between the two Teflon (registered trademark) sheets.
[0165] Thereafter, the magnetic layer was heat treated in a drying device at an internal temperature of 60° C. for 48 hours to allow the polyester urethane resin contained in the magnetic layer to undergo a crosslinking reaction with the polyfunctional isocyanate, thereby obtaining a magnetic layer. Samples for various evaluations described below were cut out from a portion of the obtained magnetic layer.
[0166] <Production of shielding materials>
[0167] The magnetic layer obtained as described above was used as the magnetic layer, and a copper foil with a thickness of 20 μm (compliant with JIS H3100: 2018 standard, alloy number C1020R-H, Cu content of 99.9 mass % or more) was used as the metal layer. The five layers of "copper foil (metal layer) / magnetic layer / copper foil (metal layer) / magnetic layer / copper foil (metal layer)" were overlapped without inserting other layers between two adjacent layers to produce a laminate.
[0168] The upper and lower plates of the plate press (large hot press TA-200-1W manufactured by YAMAMOTO ENG.WORKS Co., Ltd.) were heated to 140°C (internal temperature of the plate), the laminate was placed in the center of the plate, and a pressure of 4.66 N / mm was applied. 2 The aluminum foil and the magnetic layer were thermocompressed for 10 minutes under a pressure of . The upper and lower pressing plates were cooled to 50° C. (internal temperature of the pressing plates) while the pressure was maintained, and the laminate was taken out from the plate press.
[0169] In this way, an electromagnetic shielding material of Example 1 was obtained. The shielding material of Example 1 has two multilayer structures of "copper foil (metal layer) / magnetic layer / copper foil (metal layer)".
[0170] <Measurement of Magnetic Permeability>
[0171] A sample for measurement having a size of 28 mm × 10 mm was cut out from the magnetic layer, and the magnetic permeability was measured using a magnetic permeability measuring device (per01 manufactured by KEYCOM Corp.), and the magnetic permeability was obtained as the real part (μ') of the complex relative magnetic permeability at a frequency of 3 MHz (measurement temperature: 25° C.). The evaluation results of the magnetic permeability thus obtained according to the following evaluation criteria are shown in Table 1.
[0172] A: Magnetic permeability μ' is 100 or more
[0173] B: Magnetic permeability μ' is 40 or more and less than 100
[0174] C: Magnetic permeability μ' is less than 40
[0175] <Measurement of electrical conductivity>
[0176] A cylindrical main electrode with a diameter of 30 mm was connected to the negative electrode side of a digital super insulation resistance meter (TR-811A manufactured by Takeda Riken Industry Co., Ltd.), and a ring electrode with an inner diameter of 40 mm and an outer diameter of 50 mm was connected to the positive electrode side. The main electrode and the ring electrode were set on the sample piece of the magnetic layer cut into a size of 60 mm × 60 mm, and a voltage of 25 V was applied to both electrodes to measure the surface resistivity of the magnetic layer alone. The conductivity of the magnetic layer was calculated based on the surface resistivity and the following formula. The calculated conductivity is 1.1×10 -2 S / m.
[0177] As the thickness, the thickness of the magnetic layer obtained by the following method was used.
[0178] Electrical conductivity [S / m] = 1 / (surface resistivity [Ω] × thickness [m])
[0179] <Acquisition of Shielding Material Cross-Section Image>
[0180] The cross-section processing for exposing the cross section of the shielding material was performed by the following method.
[0181] The shielding material cut into a size of 3 mm×3 mm was embedded in a resin, and a cross section of the shielding material was cut out using an ion milling device (IM4000PLUS manufactured by Hitachi High-Tech Corporation).
[0182] The cross section of the shielding material thus exposed was observed using a scanning electron microscope (SU8220 manufactured by Hitachi High-Tech Corporation) at an acceleration voltage of 2 kV and a magnification of 100 times to obtain a reflected electron image. From the obtained image, the thickness of each of the two magnetic layers, the thickness of each of the three metal layers, and the total thickness of the shielding material were measured at 5 locations based on the scale bar. The arithmetic average of each was taken as the thickness of each magnetic layer, the thickness of each metal layer, and the total thickness of the shielding material. The thickness of each magnetic layer was 30 μm, the thickness of each metal layer was 20 μm, and the total thickness of the shielding material was 120 μm.
[0183] <Acquisition of Magnetic Layer Cross-Section Image>
[0184] Similarly to the above, in the cross section of the shield material of Example 1 exposed by cross-section processing, the magnetic layer portion was observed using a scanning electron microscope (SU8220 manufactured by Hitachi High-Tech Corporation) at an accelerating voltage of 2 kV and a magnification of 1000 times to obtain a reflected electron image.
[0185] <Measurement of aspect ratio of magnetic particles and degree of orientation of flat particles>
[0186] Using the reflected electron image obtained in the above, the aspect ratio of the magnetic particles was calculated by the method described in the above, and the flat particles were determined based on the value of the aspect ratio. As described in the above, it was determined whether the magnetic layer contained flat particles as magnetic particles, and the result was that the magnetic layer contained flat particles. In addition, for the magnetic particles determined to be flat particles, the orientation degree was calculated by the method described in the above, and the result was 13°. In addition, the average value (arithmetic mean) of the aspect ratios of all particles determined to be flat particles was calculated as the aspect ratio of the flat particles contained in the magnetic layer. The aspect ratio calculated was 0.071.
[0187] <Evaluation of shielding performance (KEC method)>
[0188] A shielding material cut into a size of 150 mm × 150 mm is set between the antennas of the KEC method evaluation device including a signal generator, an amplifier, a pair of magnetic field antennas and a spectrum analyzer, and the ratio of the received signal strength when there is no shielding material and the received signal strength when there is a shielding material at a frequency of 100 kHz is obtained as the shielding performance. This operation is performed on the magnetic field antenna to obtain the electromagnetic wave shielding performance (magnetic field wave shielding performance). In addition, KEC is the abbreviation of the Kansai Electronic Industry Promotion Center. The evaluation results of the shielding performance evaluated according to the obtained values and the following evaluation criteria are shown in Table 1.
[0189] (Evaluation Criteria)
[0190] A: 30dB or more
[0191] B: 25dB or more and less than 30dB
[0192] C: Less than 25dB
[0193] <Peel Strength>
[0194] Figure 1 and Figure 2 This is an explanatory diagram related to the measurement of peel strength.
[0195] The peel strength of the electromagnetic shielding material of Example 1 was measured by the following method.
[0196] From the electromagnetic wave shielding material of Example 1, a measurement sample having a short side length of 2.5 cm and a long side length of 5 cm was cut out.
[0197] An aluminum foil (manufactured by TAKEUCHI METAL FOIL & POWDER CO., LTD., model A1N30H-O, thickness 50 μm) having a short side length of 2.5 cm and a long side length of 15 cm was prepared.
[0198] Using an instant adhesive, the metal layer (copper foil) of one of the outermost layers of the sample for measurement and the aluminum foil were bonded so that the short sides of each foil overlapped each other, thereby creating a tension margin. This tension margin refers to the 10 cm length of the aluminum foil to which the sample for measurement is not bonded (reference Figure 1 ).
[0199] Then, the outermost metal foil (copper foil) and copper plate (manufactured by Hikari Co., Ltd., size: thickness 1 mm, short side length 5 cm, long side length 10 cm) of the other side of the above-mentioned measurement sample (i.e., the side without stretching margin) were placed in the center of the above-mentioned copper plate of the above-mentioned measurement sample and attached using double-sided tape (reference Figure 2 ).
[0200] The portion of the copper plate not attached with the electromagnetic wave shielding material is fixed to the lower chuck of the testing machine (reference Figure 2 ).
[0201] The tensile allowance was then folded back 180° and fixed to the upper chuck of the test machine, and a peel test was performed under the following measurement conditions. The peel strength calculated by dividing the load (unit: N (Newton)) obtained as the measured value by the short side length (2.5 cm) is shown in Table 1.
[0202] The peel strength measured by the above method can be said to be an index of the adhesion between two adjacent layers in the laminate, and the greater the value of the peel strength measured by the above method, the higher the adhesion between the adjacent metal layer and the magnetic layer in the electromagnetic wave shielding material. From the viewpoint of the high adhesion of the adjacent metal layer and the magnetic layer, the peel strength measured by the above method is preferably more than 0.5N / cm, more preferably more than 0.6N / cm, more preferably more than 1.0N / cm, more preferably more than 1.5N / cm, and more preferably more than 2.0N / cm. The peel strength can be, for example, less than 7.0N / cm, less than 6.5N / cm, less than 6.0N / cm, less than 5.5N / cm or less than 5.0N / cm.
[0203] (Measurement conditions)
[0204] Testing machine: Tensilon universal material testing machine (RTF-1310) manufactured by A&D Company, Limited
[0205] Measurement environment: temperature 23°C, relative humidity 50%
[0206] Force sensor: 500N (Newton)
[0207] Stretching speed: 30mm / min
[0208] <Evaluation of durability (drop peeling test)>
[0209] The electromagnetic wave shielding material of Example 1 was subjected to a drop peeling test according to the DuPont test method described in JIS-K-5600-5-3:1999. Under the conditions of an impact type, a support base radius of 6.35 mm, and a weight mass of 300 g, the drop test was performed 5 times from a height of 200 mm, and the following standards were used for evaluation. Performing the drop test 5 times means that 5 samples for measurement cut out from the electromagnetic wave shielding material of Example 1 were subjected to the drop test once for each sample (therefore, the total number of tests was 5 times).
[0210] A: No peeling was observed in 5 tests.
[0211] B: Peeling between the adjacent metal layer and magnetic layer was observed in at least one of the five tests.
[0212] C: In 5 tests, peeling between the adjacent metal layer and the magnetic layer was observed in 5 cases.
[0213] [Examples 2 to 6, Examples 9 and 10, Comparative Examples 1 and 2]
[0214] The electromagnetic shielding material was produced and various evaluations were performed by the method described in Example 1 except that the items shown in Table 1 were changed as shown in Table 1.
[0215] The thicknesses of the above-described examples and comparative examples were measured by the above-described methods. As a result, the thickness of each magnetic layer, the thickness of each copper foil (metal layer), and the total thickness of the shielding material were the same as those obtained in Example 1.
[0216] [Example 7]
[0217] As the metal layer, an aluminum foil with a thickness of 30 μm was used instead of copper foil (in accordance with JIS H4160:2006 standard, alloy number 1N30 state code (1) O, Al content 99.3 mass % or more). Otherwise, the electromagnetic wave shielding material was prepared and various evaluations were carried out by the method described in Example 1.
[0218] In this way, an electromagnetic wave shielding material of Example 7 was obtained. The shielding material of Example 7 has a two-layer structure of "aluminum foil (metal layer) / magnetic layer / aluminum foil (metal layer)".
[0219] In Example 7, various thicknesses were measured by the method described above. As a result, the thickness of each magnetic layer was 30 μm, the thickness of each metal layer was 30 μm, and the total thickness of the shielding material was 150 μm.
[0220] [Example 8]
[0221] A laminate was produced by stacking three layers of "copper foil (metal layer) / magnetic layer / copper foil (metal layer)" without interposing another layer between two adjacent layers.
[0222] The upper and lower plates of the plate press (large hot press TA-200-1W manufactured by YAMAMOTO ENG.WORKS Co., Ltd.) were heated to 140°C (internal temperature of the plate), the laminate was placed in the center of the plate, and a pressure of 4.66 N / mm was applied. 2 The aluminum foil and the magnetic layer were thermocompressed for 10 minutes under a pressure of . The upper and lower pressing plates were cooled to 50° C. (internal temperature of the pressing plates) while the pressure was maintained, and the laminate was taken out from the plate press.
[0223] Thus, an electromagnetic shielding material of Example 8 was obtained. The shielding material of Example 8 has a multilayer structure of "copper foil (metal layer) / magnetic layer / copper foil (metal layer)". Various evaluations were performed on Example 8 by the methods described in Example 1.
[0224] In Example 8, various thicknesses were measured by the method described above. As a result, the thickness of the magnetic layer and the thickness of each copper foil (metal layer) were the same as those obtained in Example 1, and the total thickness of the shielding material was 70 μm.
[0225] [Example 11]
[0226] The magnetic layer-forming composition was prepared by the method described below, and the electromagnetic shielding material was produced and various evaluations were performed by the method described in Example 1. In Table 1, the following epoxy resins are indicated as "epoxy".
[0227] <Preparation of Magnetic Layer-Forming Composition (Coating Liquid)>
[0228] Add to plastic bottles
[0229] Fe-Si-Al flat magnetic particles (Fe-Si-Al alloy MFS-SUH manufactured by MKT Corp., Ltd.): 12 g
[0230] Polyurethane resin (Nipporan 5120 manufactured by TOSOH CORPORATION, solid content concentration 30% by mass): 7.0 g
[0231] Polyfunctional isocyanate (Takenate D101E manufactured by Mitsui Chemicals, Inc., solid content concentration 75 mass %): 0.42 g
[0232] Epoxy resin (HP-A-4860 manufactured by DIC Corporation, solid content concentration 100 mass %): 0.8 g
[0233] Epoxy curing catalyst (IBMI12 manufactured by Mitsubishi Chemical Corporation, solid content concentration 100 mass %): 0.02 g
[0234] Cyclohexanone: 20g
[0235] The mixture was mixed for 1 hour using a vibration stirrer to prepare a coating solution. The content of the polyurethane resin and the content of the epoxy resin were the values shown in Table 1, based on 100 parts by mass of the total mass of the magnetic layer formed from the prepared magnetic layer-forming composition.
[0236] [Comparative Example 3]
[0237] The magnetic layer forming composition was prepared by the method described below, and an electromagnetic wave shielding material was produced by the method described in Example 1. However, the magnetic layer after applying the magnetic layer forming composition and drying had poor self-supporting properties, and the magnetic layer could not be formed, so the electromagnetic wave shielding material could not be produced.
[0238] <Preparation of Magnetic Layer-Forming Composition (Coating Liquid)>
[0239] Add to plastic bottles
[0240] Fe-Si-Al flat magnetic particles (Fe-Si-Al alloy MFS-SUH manufactured by MKT Corp., Ltd.): 12 g
[0241] Epoxy resin (HP-A-4860 manufactured by DIC Corporation, solid content concentration 75 mass %): 4 g
[0242] Epoxy curing catalyst (IBMI12 manufactured by Mitsubishi Chemical Corporation, solid content concentration 100 mass %): 0.1 g
[0243] Cyclohexanone: 25g
[0244] The mixture was mixed for 1 hour using a vibration stirrer to prepare a coating solution. The content of the epoxy resin was the value shown in Table 1, when the total mass of the magnetic layer formed from the prepared magnetic layer-forming composition was 100 parts by mass.
[0245] The above results are shown in Table 1. In Table 1, copper foil is abbreviated as "Cu", aluminum foil is abbreviated as "Al", and magnetic layer is abbreviated as "Magnetic".
[0246]
[0247] Regarding Examples 2, 9, and 10 in which the glass transition temperature Tg of the resin contained in the magnetic layer was different, an electromagnetic wave shielding material having a size of 5 cm×5 cm was produced by the method described in each Example.
[0248] The operation of bending the prepared electromagnetic wave shielding material in half by hand and then unfolding it to make it flat was repeated 5 times for each electromagnetic wave shielding material. As a result, no breakage was observed in the electromagnetic wave shielding material in Examples 2 and 9, whereas breakage was observed in the electromagnetic wave shielding material in Example 10.
[0249] Industrial Applicability
[0250] One embodiment of the present invention is useful in the technical field of various electronic components and various electronic devices.
Claims
1. An electromagnetic wave shielding material having a magnetic layer containing magnetic particles and a resin between two metal layers, The magnetic layer is in direct contact with each of the two metal layers, and The magnetic layer contains 13 parts by mass or more and less than 30 parts by mass of the urethane bond-containing resin, based on 100 parts by mass of the total mass of the magnetic layer.
2. The electromagnetic wave shielding material according to claim 1, wherein The magnetic layer contains 15 parts by mass or more and 23 parts by mass or less of the urethane bond-containing resin, based on 100 parts by mass of the total mass of the magnetic layer.
3. The electromagnetic wave shielding material according to claim 1, wherein The urethane bond-containing resin has a glass transition temperature of -60°C or higher and lower than 0°C.
4. The electromagnetic wave shielding material according to claim 1, wherein The magnetic layer further contains epoxy resin.
5. The electromagnetic wave shielding material according to claim 4, wherein When the total mass of the magnetic layer is 100 parts by mass, the total content of the urethane bond-containing resin and the epoxy group-containing resin in the magnetic layer is 15 parts by mass or more and 20 parts by mass or less.
6. The electromagnetic wave shielding material according to claim 1, wherein The electromagnetic wave shielding material includes two or more multilayer structures having the magnetic layer between two metal layers, and in each multilayer structure, the magnetic layer is in direct contact with each of the two metal layers.
7. The electromagnetic wave shielding material according to claim 1, wherein One or more of the metal layers has a Cu content of 80.0 mass % or more.
8. The electromagnetic wave shielding material according to claim 1, wherein One or more of the metal layers has an Al content of 80.0 mass % or more.
9. The electromagnetic wave shielding material according to claim 1, wherein The magnetic layer contains 15 parts by mass or more and 23 parts by mass or less of the urethane bond-containing resin, based on 100 parts by mass of the total mass of the magnetic layer. The glass transition temperature of the urethane bond-containing resin is above -60°C and below 0°C, The electromagnetic wave shielding material comprises two or more multilayer structures having the magnetic layer between two metal layers, wherein in each multilayer structure, the magnetic layer is in direct contact with each of the two metal layers, and One or more of the metal layers has a Cu content of 80.0 mass % or more.
10. The electromagnetic wave shielding material according to claim 1, wherein The magnetic layer contains 15 parts by mass or more and 23 parts by mass or less of the urethane bond-containing resin, based on 100 parts by mass of the total mass of the magnetic layer. The glass transition temperature of the urethane bond-containing resin is above -60°C and below 0°C, The electromagnetic wave shielding material comprises two or more multilayer structures having the magnetic layer between two metal layers, wherein in each multilayer structure, the magnetic layer is in direct contact with each of the two metal layers, and One or more of the metal layers has an Al content of 80.0 mass % or more.
11. The electromagnetic wave shielding material according to claim 1, wherein The magnetic layer further contains a resin containing an epoxy group, When the total mass of the magnetic layer is 100 parts by mass, the total content of the urethane bond-containing resin and the epoxy group-containing resin in the magnetic layer is 15 parts by mass or more and 20 parts by mass or less, The glass transition temperature of the urethane bond-containing resin is above -60°C and below 0°C, The electromagnetic wave shielding material comprises two or more multilayer structures having the magnetic layer between two metal layers, wherein in each multilayer structure, the magnetic layer is in direct contact with each of the two metal layers, and One or more of the metal layers has a Cu content of 80.0 mass % or more. 12 . An electronic component comprising the electromagnetic wave shielding material according to claim 1 . 13 . An electronic device comprising the electromagnetic wave shielding material according to claim 1 .
Citation Information
Patent Citations
Adhesive film
JP2015187260A
Soft magnetic flat powder
JP2018131640A
Noise suppression sheet
JP2019153623A